Ethnomedicinal Survey of Plants in the Southern District Noakhali, Bangladesh - Bhowmik, Rajesh; Saha, Monika Rani; Rahman, Md Ajijur; Islam, Md Anwar Ul (Bangladesh Pharmaceutical Journal, 2015)
Many modern medicines used today were discovered by extracting active chemicals from plants used in traditional medicine. To identify and locate any new and potential therapeutic aaplications of commonly used medicinal plants by the folk medicinal practitioners of Noakhali, Bangladesh, we conducted a survery with a semi-structured questionnaire using the guided field-walk method. Detailed information was obtained on 143 plants belonging to 62 families. Leaves were mostly used (52%) followed by roots (30.55%) and whole plants (18.74%) along with fruits, barks, seeds, stems and flowers. Gastrointestinal disorders were the most common diseases treated followed by respiratory tract infections, weakness, fever, diabetes, skin disorders, sexually transmitted diseases, hepatic disorders, pain and rheumatism. Some plants were also used for the treatment of cancer, hypertension, nerve disorders, helmenthiasis, urinary tract infections, tuberculosis, leucorrhea, edema and chicken pox. The findings of this study may help the scientists to get a comprehensive view of the folk medicinal practices in Bangladesh and can use the results to identify medicinal plants of therapeutic interests DOI: http://dx.doi.org/10.3329/bpj.v17i2.22342 Bangladesh Pharmaceutical Journal 17(2): 205-214, 2014